The Addition of "senduduk" Fruit (Melastoma malabathricum, L.) Extract as Colorants and Antioxidant on Jackfruit Straw (Artocarpus heterophyllus, L.) Jam. - Sayuti, Kesuma; Azima, Fauzan; Marisa, Melvin (International Journal on Advanced Science, Engineering and Information Technology, 2015)
Straw of jackfruit is part of a jackfruit which has not been used optimally. Jackfruit straw is rich in fiber so it can be processed into jam, but this product has a weakness in color. The addition "senduduk" fruit extract, has a lot of anthocyanin expected improving the color and antioxidant activity of the jam. In this study, it has been done addition of some level of concentration of "senduduk" fruit extract, were: 2%, 4%, 6%, 8% and 10%. The result shows, the more "senduduk" fruit extract was added, the stronger the color and the higher antioxidant activity of the Jam. Addition 8% of "senduduk" fruit extract was the best product.